1985
DOI: 10.1099/00221287-131-8-1867
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Assimilation in the Basidiomycete Yeast Sporobolomyces roseus

Abstract: Ammonium-grown cultures of Sporobolomyces roseus developed the capacity to assimilate nitrate when they were incubated in nitrate or nitrogen-free medium. Cycloheximide, 6-methyl purine and antimycin A inhibited this process. Nitrate assimilation required aerobic energy metabolism and was inhibited completely by ammonium. The rapid inhibition of nitrate assimilation by ammonium was not the result of an inhibition of nitrate reductase (NR) activity. Nitrite also inhibited nitrate assimilation. NR in cell-free e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…cylindrosporum [23]. Interestingly, the occurrence of a similar mode of regulation has been inferred previously from physiological data obtained in nitrophilic yeasts such as Sporobolomyces roseus, Candida nitratophila and Rhodotorula glutinis [40,41] and in the mycorrhizal basidiomycete Rhizopogon roseolus [11]. The above fungi colonize different environments and are not closely related evolutionarily to each other, nor to T. borchii.…”
Section: Mode Of Regulation Of Tbnrt2supporting
confidence: 67%
“…cylindrosporum [23]. Interestingly, the occurrence of a similar mode of regulation has been inferred previously from physiological data obtained in nitrophilic yeasts such as Sporobolomyces roseus, Candida nitratophila and Rhodotorula glutinis [40,41] and in the mycorrhizal basidiomycete Rhizopogon roseolus [11]. The above fungi colonize different environments and are not closely related evolutionarily to each other, nor to T. borchii.…”
Section: Mode Of Regulation Of Tbnrt2supporting
confidence: 67%
“…polyrnorpha. H. anomala showed N R activity only in the presence of nitrate, in contrast to Sporobolomyces roseus (Ali & Hipkin, 1985) and Candida nitratophilu Cannons et al, 1986) where NR was present in nitrogen-free medium. The levels of NR protein present under different conditons (Figs 2, 3 and 5) and the observed effect of cycloheximide on NR activity (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with the situation for filamentous fungi (Pateman & Kinghorn, 1976;DunnColeman et al, 1984;Wray & Kinghorn, 1989), the regulation of NR by nitrogen and carbon sources has been little studied in yeast. So far (Ali & Hipkin, 1985Cannons et al, 1986;Jones et al, 1987;Hipkin, 1989) it has been shown that NR appears in cells cultured in nitrate-containing media and is absent in ammoniumcultured cells.…”
Section: Introductionmentioning
confidence: 99%
“…These indications suggest that in this respect H . polymorpha NCYC 495 is similar to Aspergillus nidulans (Cove, 1979), Neurospora crassa (Garrett & Amy, 1978), Hansenula wingei ATCC 28162 (Jones et al, 1987), Sporobolomyces roseus (Ali & Hipkin, 1985) and H . polymorpha CBS 4732 (Gonzalez & Siverio, 1992) but differs from H .…”
Section: Discussionmentioning
confidence: 99%
“…polymorpha differs from S . roseus and C. nitratophila in that removal of ammonium from ammonium-grown cultures does not bring about ' gratuitous ' NR activities (Ali & Hipkin, 1985;Cannons et al, 1986). Thus in this yeast, NR activity does not seem to be strongly regulated by derepression.…”
Section: Discussionmentioning
confidence: 99%